2021
DOI: 10.48550/arxiv.2111.14810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mysterious Triality and Rational Homotopy Theory

Abstract: Mysterious duality has been discovered by Iqbal, Neitzke, and Vafa [INV02] as a convincing, yet mysterious correspondence between certain symmetry patterns in toroidal compactifications of M-theory and del Pezzo surfaces, both governed by the root system series E k .It turns out that the sequence of del Pezzo surfaces is not the only sequence of objects in mathematics which gives rise to the same E k symmetry pattern. We present a sequence of topological spaces, starting with the four-sphere S 4 , and then fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…dualities in string theory [Alv+94]. Recent research has found ternary analogues of these two notions of duality: a triality of vector spaces, generalizing the notion of dual pairing, in the context of the study of the SO(8) symmetry group [SPK94; Lou01; Sap01; BGR13] and a triality of equivalent theories in physics, algebraic geometry and algebraic topology [SV21].…”
Section: Biologymentioning
confidence: 99%
“…dualities in string theory [Alv+94]. Recent research has found ternary analogues of these two notions of duality: a triality of vector spaces, generalizing the notion of dual pairing, in the context of the study of the SO(8) symmetry group [SPK94; Lou01; Sap01; BGR13] and a triality of equivalent theories in physics, algebraic geometry and algebraic topology [SV21].…”
Section: Biologymentioning
confidence: 99%